2012
DOI: 10.1371/journal.pone.0042743
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Mediated Changes in Olfactory Bulb Neurogenesis and Olfactory Behavior in Male White-Footed Mice (Peromyscus leucopus)

Abstract: Brain plasticity, in relation to new adult mammalian neurons generated in the subgranular zone of the hippocampus, has been well described. However, the functional outcome of new adult olfactory neurons born in the subventricular zone of the lateral ventricles is not clearly defined, as manipulating neurogenesis through various methods has given inconsistent and conflicting results in lab mice. Several small rodent species, including Peromyscus leucopus, display seasonal (photoperiodic) brain plasticity in bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
(60 reference statements)
0
10
0
1
Order By: Relevance
“…For instance, adult-born granule cells of the OB have fewer but more stable dendritic spines in lactating mice (Kopel et al, 2012). However, there are some instances where structural plasticity does not parallel neurogenic plasticity in the OB (Walton et al, 2012). …”
Section: Information Encoded By Dg and Obmentioning
confidence: 99%
“…For instance, adult-born granule cells of the OB have fewer but more stable dendritic spines in lactating mice (Kopel et al, 2012). However, there are some instances where structural plasticity does not parallel neurogenic plasticity in the OB (Walton et al, 2012). …”
Section: Information Encoded By Dg and Obmentioning
confidence: 99%
“…However, during the short days of winter when energy conservation is critical, the attenuation of hippocampal function and associated hippocampal-mediated behaviors is likely adaptive response to conserve energy to survive the harsh energy-restricted short days of winter (Jacobs, 1996, Nelson et al, 2010, Walton et al, 2011b). These photoperiod-mediated hippocampal changes do not occur in isolation, as short day male white-footed mice have enhanced olfaction and olfactory neurogenesis, potentially to enhance winter foraging efficiency (Walton et al, 2012b). Short day mice also have enhanced amygdala function and fear memory, potentially to promote survival during winter when mice must increase foraging for food in an environment devoid of understory for cover from predation (Bratton, 1976, Walton et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to counterparts held in long summer-like day lengths, white-footed mice held in short winter-like days lengths have marked changes in cognitive ability and in the function and connectivity of underlying brain regions associated with these abilities, including olfactory memory and neurogenesis (Walton et al, 2012b), fear memory and the amygdala (Walton et al, 2012a), and spatial memory and the hippocampus (Pyter et al, 2005, Workman et al, 2009). Indeed, we have recently reported that short-day exposure impairs long term potentiation (LTP), the putative mechanism for how memories are formed and stored in the brain (Bliss and Collingridge, 1993), in the Schaffer collateral pathway of the hippocampus, and this impairment of LTP is associated with impaired spatial learning and memory (Walton et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…White-footed mice maintained in short days, but not long days, rapidly habituate to conspecific male urine. This enhanced olfactory behavior is associated with increased neurogenesis within the caudal plexiform and granule cell layers of the OB, areas known to respond to water-soluble odorants [8].…”
Section: Cognition and Memorymentioning
confidence: 99%